PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI FINANCIAL, MOTIVASI KERJA, KEPUASAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA MALL PELAYANAN PUBLIK BANYUWANGI - Devrynda Bela Anggrayny; Maslichah Maslichah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
This study aims to determine the effect of leadership style, financial compensation, work motivation, job satisfaction, and work environment on employee performance at the Banyuwangi Public Service Mall. This type of research is correlational research and is classified as quantitative research. In this study using primary data by distributing questionnaires. The sampling method used purposive sampling. The sample obtained from this study were 50 employees who met the sample criteria. The analysis used in this research is multiple linear regression. The results showed that the leadership style variable had a positive and significant effect on employee performance. The financial compensation variable has a positive and significant effect on employee performance. The variable of work motivation has a positive and significant effect on employee performance. And the variable job satisfaction has a positive and significant effect on employee performance.Keywords: Leadership Style, Financial Compensation, Work Motivation, Job Satisfaction, Work Environment and Employee Performance